Efficacy of fibre additions to flatbread flour mixes for reducing post-meal glucose and insulin responses in healthy Indian subjects. Issue 3 (6th March 2017) - Boers, Hanny M.; MacAulay, Katrina; Murray, Peter; Dobriyal, Rajendra; Mela, David J.; Spreeuwenberg, Maria A. M.
Abstract: The incidence of type 2 diabetes mellitus (T2DM) is increasing worldwide, including in developing countries, particularly in South Asia. Intakes of foods generating a high postprandial glucose (PPG) response have been positively associated with T2DM. As part of efforts to identify effective and feasible strategies to reduce the glycaemic impact of carbohydrate-rich staples, we previously found that addition of guar gum (GG) and chickpea flour (CPF) to wheat flour could significantly reduce the PPG response to flatbread products. On the basis of the results of an exploratory study with Caucasian subjects, we have now tested the effect of additions of specific combinations of CPF with low doses of GG to a flatbread flour mix for their impacts on PPG and postprandial insulin (PPI) responses in a South-Asian population. In a randomised, placebo-controlled full-cross-over design, fifty-six healthy Indian adults consumed flatbreads made with a commercial flatbread mix (100 % wheat flour) with no further additions (control) or incorporating 15 % CPF in combination with 2, 3 or 4 % GG. The flatbreads with CPF and 3 or 4 % GG significantly reduced PPG (both ≥15 % reduction in positive incremental AUC, P <0·01) and PPI (both ≥28 % reduction in total AUC, P <0·0001) compared with flatbreads made from control flour. These results confirm the efficacy and feasibility of the addition of CPF with GG to flatbread flour mixes to achieve significant reductions in both PPG and PPI in Indian subjects.